2018
DOI: 10.1080/0284186x.2018.1481292
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiation therapy (SBRT) improves local control and overall survival compared to conventionally fractionated radiation for stage I non-small cell lung cancer (NSCLC)

Abstract: SBRT compared to CONV is associated with improved LF rates and OS. Our data supports the continued use and expansion of SBRT as the standard of care treatment for inoperable early-stage NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 26 publications
(29 reference statements)
2
31
0
Order By: Relevance
“…It can deliver high doses to relatively small target lesions, thus achieving more than 90% local control and substantially improving prognosis with a low risk of toxicity [18]. Of note, SBRT has been demonstrated to have remarkable advantages over conventional radiotherapy, potentially due to its more potent immune activation effects [19,20]. Several studies have observed that radiation-induced antitumor immunity might be dose-dependent, with relatively higher doses being more powerful immunologic adjuvants [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…It can deliver high doses to relatively small target lesions, thus achieving more than 90% local control and substantially improving prognosis with a low risk of toxicity [18]. Of note, SBRT has been demonstrated to have remarkable advantages over conventional radiotherapy, potentially due to its more potent immune activation effects [19,20]. Several studies have observed that radiation-induced antitumor immunity might be dose-dependent, with relatively higher doses being more powerful immunologic adjuvants [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Multimodality treatment of non-small cell lung cancer (NSCLC) has become more effective in recent years, e.g., due to stereotactic ablative radiotherapy for stage I disease [1,2] and oligometastatic stage IV disease [3][4][5], and immunotherapy for stage III and IV disease [6,7]. Patients with stage III disease who are unfit for radical chemoradiotherapy should be considered for reduced-intensity palliative chemoradiotherapy [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…3 For patients with localized disease who refuse surgery or are deemed medically inoperable, stereotactic body radiation therapy (SBRT) is a nonsurgical treatment option which has very high local control rates. [4][5][6] With its ablative nature, SBRT employs large fraction doses in combination with small margins to deliver very high doses to the target while sparing much of the surrounding tissues. For lung lesions, target motion associated with respiration can complicate the situation.…”
Section: Introductionmentioning
confidence: 99%